MENELAAH KEBIJAKAN DINAS SOSIAL DAN PEMAKAMAN ATAS HAK-HAK ANAK DI KOTA PEKANBARU - Kasmanto Rinaldi; Andriyus Andriyus (UIR Press, 2018)
One of the social welfare problems that are still flourish in Pekanbaru today is neediness children. Children are a trust and the gift of the Almighty God, whose in they inherent dignity as human beings. Likewise, children are the next generation the ideals of the struggle of a nation that has a strategic role and have special characteristics and properties that are expected to ensure the continued existence of the nation and the State in the future. Given the position and hope to the children as the potential and future of the nation so that the child may deserve the attention of all parties so that children can grow and develop naturally and avoid the treatment and the wrong action, violence, discrimination which would undermine the development of the child, whether physical, mental and social development. Therefore they need to get the widest possible opportunity to grow and develop optimally both physically, mentally, socially for the realization of quality child, noble and prosperous. In fact, we could see the number of neediness children who spend time in the intersection traffic light and the other crowded places in the city of Pekanbaru. This is the bitter of the truth, children of their age should have been more at home gets the attention and affection of parents, school and play with peers, but they spend more time outside of their home where is on the streets and other public places for various reasons. From the results of the research on policy implementation Social Service and Funerary of Pekanbaru in protecting the rights of children which is based on the concept of Van Meter and Van Horn, it can be concluded that of the six indicators seen there are several sub-indicators are still not good that the budget provision, the provision of facilities supporters, the response of the executive is not maximized and the character of the target group who do not want to be fostered.